2017
DOI: 10.1093/abbs/gmx067
|View full text |Cite
|
Sign up to set email alerts
|

Effects of trigonelline inhibition of the Nrf2 transcription factor <italic>in vitro</italic> on <italic>Echinococcus granulosus</italic>

Abstract: The aim of this study was to investigate the impact of trigonelline (TRG) on Echinococcus granulosus, and to explore the inhibition impact of nuclear factor erythroid-2-related factor 2 (Nrf2) signaling pathway on E. granulosus protoscoleces. Echinococcus granulosus protoscoleces were incubated with various concentrations of TRG, and then Nrf2 protein expression and its localization in protoscoleces were detected by western blot analysis and immunofluorescence assay, respectively. Reactive oxygen species (ROS)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 66 publications
1
4
0
Order By: Relevance
“…To date, a parasiticidal ideal agent that is both effective and riskless has not been identified. Our previous experiments confirmed that the use of MAPK or Nrf2 signaling pathway inhibitors can affect PSCs viability by denaturing and structurally disrupting the E. granulosus PSCs [ 24 , 25 ]. The purpose of this study was to elucidate the association between MAPK and Nrf2 signaling pathways in vitro in E. granulosus , which may be useful in providing areas for more drug research in the treatment of CE.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…To date, a parasiticidal ideal agent that is both effective and riskless has not been identified. Our previous experiments confirmed that the use of MAPK or Nrf2 signaling pathway inhibitors can affect PSCs viability by denaturing and structurally disrupting the E. granulosus PSCs [ 24 , 25 ]. The purpose of this study was to elucidate the association between MAPK and Nrf2 signaling pathways in vitro in E. granulosus , which may be useful in providing areas for more drug research in the treatment of CE.…”
Section: Discussionsupporting
confidence: 71%
“…Gu et al [23] found that propofol-induced protection of human neuroblastoma cells (SH-SY5Y) against H 2 O 2 is associated with HO-1 via the ERK Pathway. Our previous study has confirmed that MAPK and Nrf2 are both expressed in E. granulosus PSCs and play an important role in the growth and development of E. granulosus [24,25]. Under the stimulation of other injurious effects of oxidative stress, the interaction between MAPK and Nrf2/HO-1 signaling pathways in E. granulosus has not been established experimentally.…”
Section: Introductionmentioning
confidence: 93%
“…As a prelude to examining whether SFX-01 also achieves its effects on osteoclasts via the modulation of NFR2, our studies were initially focused on whether pharmacological NRF2 modulators, namely Trig and RA839, exerted direct effects on osteoclast formation and function. The alkaloid, Trig, has been used in many studies as an inhibitor of NRF2 in other cell types [41][42][43]. On the other hand, RA839 has only recently been characterised as a non-covalent KEAP1 binding partner and selective activator of NRF2 [44]; neither have been used in assays of osteoclastogenesis previously.…”
Section: Discussionmentioning
confidence: 99%
“…TRG showed an impact on parasites such as Echinococcus granulosus which caused cystic echinococcosis or hydatid disease in various organs in humans. TRG could induce damage to Echinococcus granulosus protoscoleces, including hook deformation, lesions, and digitiform protuberances, by decreasing Nrf2, NQO-1, and HO-1 expression and increasing caspase-3 activity [ 103 ].…”
Section: Antiviral Antimicrobial and Antifungal Effects Of Trgmentioning
confidence: 99%